Synthesis and Crystal Structure of 3D-Superamolecular Zinc Complex Derived from Pyridine-2,5-dicarboxylate and Oxalate - Yang, Ting-Hai (2017)
A novel complex, Zn-2(Hpdc)(2)(Ox)(H2O)(4)] (H(2)pdc = pyridine-2,5-dicarboxylic acid, Ox = oxalate), has been hydrothermally synthesized and characterized by the elemental analyses, IR spectrum and single crystal X-ray diffraction. Crystal structure analysis reveals that the compound crystallizes in monoclinic space group P2(1)/n, features an interesting 3D-supramolecular network via hydrogen bonding and pi-pi stacking interactions. Cell unit parameter for the compound: a = 10.2152(3) angstrom, b = 9.6535(3) angstrom, c = 10.3594(2) angstrom, beta = 105.664 degrees, V = 983.63(5) angstrom(3), Z = 2, M-r = 623.05, D-c = 2.104 g/cm(3), mu = 2.536 mm(-1), F-(000) = 628, T = 150(2) K, R = 0.0356, wR = 0.0612 for 2510 reflections with I > 2 sigma(I).